The Impact of Price-Level Adjustment in the Context of Risk Assessment - Short, Daniel G. (Journal of Accounting Research, 1978)
Daniel G. Short, The Impact of Price-Level Adjustment in the Context of Risk Assessment, Journal of Accounting Research, Vol. 16, Studies on Changes in General and Specific Prices: Empirical Research and Public Policy Issues (1978), pp. 259-272